U2 small nuclear RNA auxiliary factor 2, transcriptionally activated by the transcription factor Dp-1/E2F transcription factor 1 complex, enhances the growth and aerobic glycolysis of leiomyosarcoma cells. Issue 4 (1st April 2022) - Li, Yuguo; Chen, Sihao; Zhang, Xin; Zhuo, Naiqiang
ABSTRACT: The dysregulation of U2 Small Nuclear RNA Auxiliary Factor 2 (U2AF2) is associated with malignant behaviors of multiple types of tumors. In this study, we explored the association between U2AF2 dysregulation and the survival of patients with primary leiomyosarcoma, the regulatory effect of U2AF2 on cell growth/aerobic glycolysis, and the mechanisms of U2AF2 dysregulation at the transcriptional level. Gene expression and survival time of patients with primary leiomyosarcoma were extracted from TCGA-Sarcoma (SARC). Leiomyosarcoma cell lines SK-LMS-1 and SK-UT-1 were utilized to construct in vitro and in vivo models. Results showed that the higher U2AF2 expression group had significantly shorter progression-free survival (HR: 2.049, 95%CI: 1.136–3.697, p = 0.011) and disease-specific survival (4.656, 95%CI: 2.141–10.13, p < 0.001) compared to the lower U2AF2 expression group. U2AF2 knockdown suppressed leiomyosarcoma cell growth and aerobic glycolysis (decreased glucose uptake, lactate production, and extracellular acidification rate) in vitro . Tumors derived from SK-LMS-1 cells with U2AF2 knockdown grew significantly slower, with lower GLUT1, PGK1, and PGAM1 protein expression than the control groups. TFDP1 and E2F1 could interact with each other in leiomyosarcoma cells. Both TFDP1 and E2F1 could bind to the promoter of U2AF2 and exert a synergistic activating effect on U2AF2 transcription. In conclusion, this study revealed that U2AF2 upregulation is associated with poor survival of leiomyosarcoma. Its upregulation enhances proliferation and aerobic glycolysis of leiomyosarcoma cells in vitro and in vivo . TFDP1 and E2F1 can form a complex, which binds to the U2AF2 gene promoter and synergistically activates its transcription. Graphical Abstract: uf0001